2016
DOI: 10.31266/at.v31i1.1393
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Kelistrikan Plasma Pijar Korona Menggunakan Elektroda Multi Titik-Bidang Dalam Perlakuan Tekstil

Abstract: ABSTRAKStudi awal karakteristik arus listrik sebagai fungsi tegangan pada daerah plasma pijar korona untuk perlakuan bahan tekstil telah dilakukan menggunakan reaktor plasma berkonfigurasi multi-titik bidang. Penelitian dilakukan dengan membandingkan karakteristik arus-tegangan pada reaktor plasma pijar korona tanpa dan dengan bahan kain tekstil. Selain itu, penelitian ini juga mengkaji karakteristik arus-tegangan dengan metode input tegangan naik dan tegangan turun. Plasma pijar korona dibangkitkan di antara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…This explains Figure 4 and 5 that the low efficiency of waste degradation and color removal occurred at 5.0 cm distance between the electrodes. These results are in accordance with the research carried out by [16] which showed a similar effect on the corona plasma experiment to modify the absorbency of cotton and polyester fabrics. Based on the experimental results, the optimum distance between the electrodes for treating textile wastewater with plasma corona discharge was at a distance of 4.0 cm.…”
Section: Effect Of Electrodes Distance On Cod and Color Removal Effic...supporting
confidence: 92%
See 1 more Smart Citation
“…This explains Figure 4 and 5 that the low efficiency of waste degradation and color removal occurred at 5.0 cm distance between the electrodes. These results are in accordance with the research carried out by [16] which showed a similar effect on the corona plasma experiment to modify the absorbency of cotton and polyester fabrics. Based on the experimental results, the optimum distance between the electrodes for treating textile wastewater with plasma corona discharge was at a distance of 4.0 cm.…”
Section: Effect Of Electrodes Distance On Cod and Color Removal Effic...supporting
confidence: 92%
“…A series of experiments were carried out in a plasma corona discharge reactor with a needle-shaped point-plane electrode made of copper with a pointed tip placed on the surface of the textile wastewater at a specified distance (Figure 1) [16]. The number of needles attached to the point electrode was 60 points with a needle length of 3.0 cm.…”
Section: Experimental Procedures and Analysismentioning
confidence: 99%
“…4 Selain dengan menggunakan tipe DBD, perlakukan kain dengan iradasi plasma juga telah dilakukan dengan jenis lucutan plasma pijar korona positif. 5 Pembangkitan plasma pijar korona positif ini menggunakan elektroda bergeometri titik-bidang dimana elektroda titik diperlakukan sebagai anoda. Hal ini menyebabkan partikel-partikel plasma bermuatan postif akan terdeposisi ke kain katun dan poliester yang diletakkan di katoda.…”
Section: Pendahuluanunclassified